2014
DOI: 10.1021/es501674p
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Environmental Partitioning Properties of Nonpolar Complex Mixtures by Use of GC × GC

Abstract: Comprehensive two-dimensional gas chromatography (GC × GC) is effective for separating and quantifying nonpolar organic chemicals in complex mixtures. Here we present a model to estimate 11 environmental partitioning properties for nonpolar analytes based on GC × GC chromatogram retention time information. The considered partitioning properties span several phases including pure liquid, air, water, octanol, hexadecane, particle natural organic matter, dissolved organic matter, and organism lipids. The model tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
88
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(91 citation statements)
references
References 125 publications
3
88
0
Order By: Relevance
“…We excluded ionized species from this data because our proposed models, PPM and GC×GC model, can theoretically account for the intermolecular interactions for neutral organic chemicals only. This resulted into a data size of 175 neutral organic chemicals, and is shown in For the GC×GC model, a two-parameter LFER equation was calibrated using retention parameters ( 1 , 2 ) that were estimated for a set of 79 model nonpolar chemicals following the approach developed elsewhere 26,27 . The model training set (Table S3) is formulated to span several nonpolar families in a balanced way.…”
Section: Data Source and Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…We excluded ionized species from this data because our proposed models, PPM and GC×GC model, can theoretically account for the intermolecular interactions for neutral organic chemicals only. This resulted into a data size of 175 neutral organic chemicals, and is shown in For the GC×GC model, a two-parameter LFER equation was calibrated using retention parameters ( 1 , 2 ) that were estimated for a set of 79 model nonpolar chemicals following the approach developed elsewhere 26,27 . The model training set (Table S3) is formulated to span several nonpolar families in a balanced way.…”
Section: Data Source and Analysismentioning
confidence: 99%
“…The model training set (Table S3) is formulated to span several nonpolar families in a balanced way. Then, the GC×GC model was validated independently using a set of 52 nonpolar chemicals (Table S4), which were analyzed on the GC×GC instrument in previous studies 26,27 . The experimental values of for the nonpolar chemicals in the training and validation sets for the GC×GC model were not available.…”
Section: Data Source and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Scientists were able to identify known skin penetrants in environmental samples such as the household dust using comprehensive two-dimensional liquid chromatography coupled with time-of-flight mass spectrometry 25 . In addition to its separation power, recent studies 26,27,28 demonstrated the potential of GC×GC in chemical risk assessment.…”
Section: Introductionmentioning
confidence: 99%
“…GC × GC is considered an established separation technique and for the last decade focus has shifted away from the development of modulation technology to applying the technique to an ever increasing number of analytical challenges. Fields in which GC × GC applications are popular include petroleum and petrochemicals [6][7][8][9][10][11][12][13][14][15][16]; food, flavours and fragrances [17][18][19][20][21][22][23][24][25][26][27][28][29][30]; metabolomics [31][32][33][34][35][36][37][38][39][40][41][42] and environmental analysis [43][44][45][46][47][48][49]. Although GC × GC has never been more widespread, there are some applications that remain challenging for a chromatographer to perfect.…”
Section: Introductionmentioning
confidence: 99%